2014
DOI: 10.1016/j.juro.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Killed but Metabolically Active Mycobacterium bovis bacillus Calmette-Guérin Retains the Antitumor Ability of Live bacillus Calmette-Guérin

Abstract: Our results suggest that killed but metabolically active bacillus Calmette-Guérin could be considered a safer immunotherapy alternative to treatment with the live bacillus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…M. brumae shows in vitro, ex vivo, and in vivo an antitumor ability similar to that of BCG 13 . Second, we have demonstrated in vitro and ex vivo the antitumor activity of killed but metabolically active BCG 14 . In contrast to the proposal of using cell wall extracts, the use of killed but metabolically active-mycobacteria implies using the whole bacterium, thus avoiding missing any potential immunostimulatory compounds.…”
Section: Introductionmentioning
confidence: 91%
“…M. brumae shows in vitro, ex vivo, and in vivo an antitumor ability similar to that of BCG 13 . Second, we have demonstrated in vitro and ex vivo the antitumor activity of killed but metabolically active BCG 14 . In contrast to the proposal of using cell wall extracts, the use of killed but metabolically active-mycobacteria implies using the whole bacterium, thus avoiding missing any potential immunostimulatory compounds.…”
Section: Introductionmentioning
confidence: 91%
“…Unlike the observations made by the above mentioned authors, other authors found that HK BCG had no inhibitory effect in MGH BC cells [69]. Moreover, lower cytokine levels were produced by HK and γ-irradiated mycobacteria-infected cells than those infected by live bacteria [63,69]. Between both treatments, γ-irradiated mycobacteria trigger cytokine levels closer to those induced by live mycobacteria, than those induced by HK mycobacteria.…”
Section: Purified Mycobacteria Antigens and Non-viable Mycobacteriamentioning
confidence: 69%
“…Between both treatments, γ-irradiated mycobacteria trigger cytokine levels closer to those induced by live mycobacteria, than those induced by HK mycobacteria. Regarding immune activation: induction of cytotoxicity by activated cells, induction of cytokine production, and expression of activation markers on immune cells, again the immune response induced by live mycobacteria was higher than that triggered by non-viable mycobacteria [63,66,70,71].…”
Section: Purified Mycobacteria Antigens and Non-viable Mycobacteriamentioning
confidence: 95%
See 2 more Smart Citations